2012
DOI: 10.1007/s12325-012-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Lipid Profile of Dipeptidyl Peptidase 4 Inhibitors, Pioglitazone, Acarbose, and Sulfonylureas: Meta-analysis of Placebo-Controlled Trials

Abstract: The present meta-analysis shows that available glucose-lowering drugs may have varying effects on the lipid profile. DPP-4 inhibitors, acarbose, and pioglitazone seem to have a more favorable effect on the lipid profile than sulfonylureas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 48 publications
8
49
1
1
Order By: Relevance
“…Although previous studies have demonstrated that DPP-4 inhibitors might have a favorable effect on the lipid profile [17], the combination therapy with sitagliptin and glimepiride did not change level of LDL cholesterol or TG in this study.…”
Section: Discussioncontrasting
confidence: 94%
“…Although previous studies have demonstrated that DPP-4 inhibitors might have a favorable effect on the lipid profile [17], the combination therapy with sitagliptin and glimepiride did not change level of LDL cholesterol or TG in this study.…”
Section: Discussioncontrasting
confidence: 94%
“…The effect on total cholesterol is less clear but a recent meta-analysis reported that treatment with this drug was associated with a significant reduction in total cholesterol [35]. Furthermore, it is known that pioglitazone modifies LDL particle size, reducing its atherogenic effects [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent meta-analyses indicated modest reductions in fasting LDL-C, total cholesterol, and TG with small or no significant improvement in HDL-C following chronic treatments with GLP-1R agonists (12)(13)(14) or DPP-4 inhibitors (13,15). For example, treatment with exenatide or liraglutide for several weeks to 3 years reduced fasting levels of TG, total cholesterol and LDL-C, increased HDL-C (16)(17)(18)(19); and reduced fasting apoB (19)(20)(21)(22), apoB-48 (a surrogate measure of intestinal lipoprotein particle numbers) (23), and free fatty acid (FFA) (24)(25)(26).…”
Section: Glp-1r Agonists Improve Fasting and Postprandial Lipid Profimentioning
confidence: 99%